Strategic Innovation in Accounting Ethics: How Religious Spirituality Shapes Competitive Advantage in Developed and Developing Countries - Nur Farizha; Mutmainnah; Ernawaty Usman; Jurana; Mustamin (Journal of Strategic Innovation in Economics and Business, 2025)
The global accounting profession is currently navigating a profound crisis of confidence, necessitating a shift from mere regulatory compliance to a holistic integration of ethical values within the strategic core of organizations. This study investigates the intersection of religious spirituality and accounting ethics, exploring how "spiritual capital" serves as a catalyst for sustainable competitive advantage across diverse economic contexts. Employing an integrative literature review methodology, the research synthesizes contemporary scholarship and theoretical frameworks, specifically the Resource-Based View (RBV) and Institutional Theory, to analyze data collected from the Scopus database (2004–2024). The findings reveal a distinct dichotomy in how spirituality shapes strategic outcomes: in developed economies, religious spirituality functions as a mechanism for differentiation and talent retention, mitigating professional alienation in high-pressure environments. In contrast, in developing economies, spirituality acts as a vital informal institution that fills "institutional voids," substituting for weak legal enforcement by providing the normative scaffolding for trust and social legitimacy. Furthermore, the study introduces the concept of "Spiritual Strategic Innovation," identifying Integrated Reporting (IR) as a technical manifestation of spiritual stewardship. This research concludes that spiritual capital is a valuable, rare, and inimitable resource that enables firms to transform accounting into a strategic engine for the common good. The implications suggest a need for a "polycentric" approach to global accounting ethics that respects localized spiritual values to enhance organizational resilience.